Need for Closure Moderates the Break in the Message Effect - Dolinski, Dariusz; Dolinska, Barbara; Bar-Tal, Yoram (Frontiers in Psychology, 2016)
Abstract Cutting the message into smaller portions is a common practice in the media. Typically such messages consist of a headline followed by a story elaboration. In a series of studies Dolinski and Kofta (2001) have shown that such a break in the message increases the effect of the information provided in the headline over that of a story which actually contained information inconsistent with that headline. A possible explanation of this effect, based on the concept of the need for cognitive closure, is presented in the article. The experiment shows the break-in-the-message effect is found mainly for participants with high need for closure but not for those with low such need.